Physical-Verbal Aggression and Depression in Adolescents: The Role of Cognitive Emotion Regulation Strategies - Rey Peña, Lourdes; Universidad de Málaga (2012)
The present study examined the relationships between the use of cognitive emotion regulation strategies, physical-verbal aggression and depression in a sample of 248 adolescents. Specific emotion regulation strategies such as acceptance, rumination and catastrophizing explained significant variance in depression in adolescents. With respect to physical-verbal aggression, our results showed that the use of self-blame and rumination only predicted levels of aggression in boys but not girls. Regarding gender differences, girls tend to ruminate and to report more catastrophic thoughts than boys. Our findings suggest a profile of cognitive emotion regulation strategies related to physical-verbal aggression and depressive symptoms which might be taken into account in future socio-emotional learning programs for adolescents.